The Experience of Using of Social and Creative Activity in the Psychological Rehabilitation of People with Disabilities - Romanovsky N.V (Moscow State University of Psychology and Education, 2019)
The article aim is analyzing the effect of innovative ergo and art therapy techniques "Ebru" in the social and creative rehabilitation of people with severe movement disorders using the example of working with a young man (26 years old) with a with spinal cord injury. The article gives a detailed description of this technique, which is the best suited for people with such disorders, because it is quite easy to learn, for drawing it is not necessary to be able to carry out subtle differentiated movements of the hands. The article describes the rehabilitation strategy used, identifies the advantages and limitations when working with this category of persons with disabilities, defines the conditions under which the advantages of the method can be fully realized. In order to study the personality characteristics of the rehabilitant, psychological diagnostics was carried out using the methods: Dembo-Rubinshtejn self-assessment method, questionnaire "Quality of life" (S. Kreitler), test "Life Orientation Test", test of hardiness, method "Dreams, hope, fears and anxiety" (A.M. Prikhozhan), and "Tree" method. The environmental resources of the rehabilitant are also analyzed. The question about creation a complex rehabilitation environment is raised.